2008
DOI: 10.1177/0269215507086181
|View full text |Cite
|
Sign up to set email alerts
|

Handle size as a task constraint in spoon-use movement in patients with Parkinson's disease

Abstract: These results suggest that, for people with Parkinson's disease, a small-to-medium-sized handle is more suitable than a large-sized built-up handle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…Modified spoon handles can be beneficial while feeding and research has shown positive outcomes regarding the potential benefits of these utensils for patients with conditions including rheumatoid arthritis, Parkinson’s disease, and cerebral palsy ( Ma et al, 2008 ; Van Roon & Steenbergen, 2006 ). Handle diameter and its relationship to spoon-use movement was examined in patients with Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Modified spoon handles can be beneficial while feeding and research has shown positive outcomes regarding the potential benefits of these utensils for patients with conditions including rheumatoid arthritis, Parkinson’s disease, and cerebral palsy ( Ma et al, 2008 ; Van Roon & Steenbergen, 2006 ). Handle diameter and its relationship to spoon-use movement was examined in patients with Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…The power grip is a common grip used among typically developing young children [25,26] as well as children [19] and adults [16,17] with motor impairments due to neurological conditions. Due to limited range of motion in the wrist in the frontal plane (radial/ulnar deviation), this grip type allows for a smaller variety of movements [27].…”
Section: Methodsmentioning
confidence: 99%
“…Self-feeding is one of several self-care activities that are critical for the well-being of a child [15], hence it is an important skill to train, develop and monitor in children with motor disorders [13]. Furthermore, self-feeding kinematics is altered in people with neurological conditions, such as Parkinson's disease [16], stroke [17], or Multiple Sclerosis [18], and in children [19] and adults [20] with cerebral palsy. Specifically, both spatial and temporal patterns of reaching with a utensil to the mouth may be altered and movements are slower, more curved and less smooth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrogoniometers have previously been found to be a valid and reliable tool for the measurement of ROM (Bronner et al 2010;Carnaz et al 2013;Piriyaprasarth et al 2008 Manuscript to be reviewed held devices, such as mobile phones, and found the electrogoniometer to be both clinically feasible and accurate (Jonsson et al 2007). Modified spoon handles can be beneficial while feeding and research has shown positive outcomes regarding the potential benefits of these utensils for patients with conditions including rheumatoid arthritis, Parkinson's disease, and cerebral palsy (Ma et al 2008;van Roon & Steenbergen 2006). Handle diameter and its relationship to spoon-use movement was examined in patients with Parkinson's disease.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%